Immersive learning: the use of a virtual simulated newsroom on Second Life - Santos, Ana (2020)
The study main purpose is to identify in what extent a virtual simulated newsroom in Second Life could influence the practical knowhow of the journalism students. All the students involved took pre and post surveys and underwent direct observation. The results analysed showed that in spite of many technological handicaps students had a better performance concerning best newsroom practices, the results also indicated that online students learned just as much as in a face to face situation and also that students enjoyed the teaching and learning experience better than the traditional way. The investigation took under consideration some of the latest studies concerning e-learning and b-learning strategies. The teaching/learning experience selected for this case study provided a good opportunity to evaluate some different online teaching/learning methods. As the main study focus was about practical behaviours this popular virtual 3-D platform showed to be a very handy tool to develop some of the Journalism course curricular.